Problem solving and uncertainty modeling through optimization and soft computing applications - Saxena, Pratiksha; Singh, Dipti 1980-; Pant, Millie 1979- (Advances in computational intelligence and robotics (ACIR) book series, 2016)
Presents the latest research trends and developments in the area of applied optimization methodologies and soft computing techniques for solving complex problems. Taking a multi-disciplinary approach, this critical publication is an essential reference source for engineers, managers, researchers, and post-graduate students